Comparison of the novel Uroquattro HB&LTM system and classical phenotypic method for rapid screening of multidrug-resistant organism colonization at the University Hospital Centre Split, Croatia : Usporedba nove brze metode Uroquattro HB&LTM s klasičnom fenotipskom metodom probira kliconoštva višestruko-otpornim organizmima u Kliničkom bolničkom centru Split, Hrvatska - Marinović, Jelena (Array, 2020)
Background. Infections caused by multidrug-resistant organisms (MDRO) are difficult to treat and associated with poor outcomes for patients. Therefore, early identification and management of colonization are essential as first steps in infection prevention. Culture-based methods have been widely used for MDRO screening. The turnaround time (TAT) for the identification of carriers varies between 48-72 h with this method. The aim of our study was to compare the performance of the new rapid semiautomatic method for detection of MDRO (HB&L Uroquattro, Alifax) with standard cultivation on selective media. Methods. Twenty-one axillary, 20 nose and 19 rectal swabs were taken in duplicate on two selected days at the University Hospital Centre Split, Croatia. Swabs were cultivated and MDRO isolates were identified on selective media (Chromagar MRSA and Chromagar ESBL) according to the standard operating procedure. Novel Alifax method was performed according to manufacturer’s instructions. Results. TAT for the new method was significantly lower (6.5 h) in comparison to the classical method. With classical method, 10 extended spectrum ß-lactamases (ESBL) producing strains from 10 different rectal specimens were isolated on Chromagar ESBL media. Exactly the same specimens were positive for the presence of ESBL-producing bacteria by rapid Alifax method. On selective Chromagar MRSA media, 11 MDRO were isolated, while rapid method detected 11 MDRO from the same specimens. Conclusions. High concordance of positive and negative results obtained with classical and rapid method is encouraging. However, our study was performed on a small sample size and further research with larger sample size is needed.